Findings from the expert-novice paradigm on differential response behavior among multiple-choice items of a pedagogical content knowledge test – implications for test development - Lieberei, Tobias; Welter, Virginia Deborah Elaine; Großmann, Leroy; Krell, Moritz (Frontiers in Psychology, 2023)
Pedagogical content knowledge (PCK) is one core dimension of teachers’ professional knowledge and comprises knowledge about conceptual ideas of learners and appropriate instructions. However, several challenges regarding the assessment of PCK are discussed in the literature: For example, PCK is a topic-specific construct and contains differentiable subdomains, which must be considered during test development. In addition, the choice of test type needs to be considered. While open-ended instruments can capture a broader range of cognitions, they often require a high level of interpretation; in contrast, multiple-choice instruments have advantages in terms of objectivity and test economy. Some challenges of assessing PCK are particularly related to multiple-choice instruments, such as an insufficient focus on specific components or the accidental assessment of teachers’ beliefs instead of PCK. To better understand and explain these challenges in developing multiple-choice PCK instruments, we exemparly used an instrument to assess PCK about scientific reasoning and considered the assumptions of the expert-novice paradigm to analyze differential response behavior between n = 10 researchers in the field of biology education (experts) and n = 10 undergraduate pre-service biology teachers (novices). As expected, experts scored significantly higher than novices. At the same time, experts answered the items more consistently than novices, i.e., showed less variance. However, the difference found was statistically insignificant. Regarding the explanations for choosing a response option, experts more often correctly identified the quintessence of the items, which means that they more often understand the items as intended and argued based on their PCK. On the other hand, novices focused more on surface characteristics, i.e., they argued rather with surface knowledge like intuition or personal experience, than choosing the response option based on their PCK. These crucial differences in how experts and novices understand the items of the used PCK instrument and how they respond based on their understanding affect different test characteristics. In conclusion, we recommend ensuring that instruments address only a few, specific PCK aspects, considering the target group of a test, and take into account that target groups with larger variability among their responses require a higher number of items to achieve satisfactory discrimination and reliability indices.